Structural effects of the bioavailable fraction of pesticides in soil: suitability of elutriate testing - Antunes, Sara C. (2020)
This study focused the ecotoxicological evaluation of four different pesticides (chlorpyrifos, glyphosate, vinclozolin, endosulfan), sprayed into an agricultural soil, using a standard battery of aquatic bioassays for testing of soil elutriates: Vibrio fischeri -Microtox(®); Pseudokirchneriella subcapitata growth inhibition; Daphnia magna acute and chronic toxicity. Despite relevant pesticide residues were recovered from the soil matrix (concentrations higher than 1000 μg kg(-1)), much lower concentrations could be retrieved from elutriates (highest records for endosulfan of ca. 250 ng L(-1)and 1400 ng L(-1); dissolved and particulate concentration, respectively) and little effects were generally found in the bioassays. Lethal effects (D. magna 48 h-EC50 of 36.8%) could be noticed following exposure to the endosulfan elutriate. Elutriates induced no toxicity on V. fischeri; algal growth was generally inhibited at high elutriate dilutions and stimulated at the lower elutriate dilutions; and no overall impairment of D. magna life-history was noticed. Results revealed that cross-contamination during field application, input of organic matter and nutrients by elutriates in test solutions, and choice of test species and endpoints may constrain the ecotoxicological assessment. Suitability of established aquatic bioassay test batteries for these purposes, and questioning on whether direct assays with soil organisms could be more protective tools is discussed.